Science Mapping Research of the Integration of PjBL Model and STEM Approach: A Bibliometric Analysis - Rizqa Kariyma; Asrizal Asrizal; Harman Amir; Fauziah Ulmi; Azifa Feziyasti (Journal of Innovative Physics Teaching, 2026)
Integration of Project-Based Learning (PjBL) with the Science, Technology, Engineering, and Mathematics (STEM) approach has gained increasing attention in science education due to its potential to develop 21st-century skills. However, studies examining the development and research directions of the integration of these two approaches have not yet been comprehensively mapped. This study aims to analyze trends, collaboration patterns, and thematic focuses in research related to the integration of PjBL and STEM in science education. This study employs a bibliometric approach using data obtained from Scopus-indexed articles published between 2015 and 2025. The analysis was conducted using VOSviewer through performance analysis, co-authorship, keyword co-occurrence, and thematic mapping. The results indicate a significant increase in the number of publications, with primary focuses on the development of 21st-century skills, student engagement, and contextual learning. Research collaboration remains relatively limited but is beginning to expand internationally. The integration of PjBL and STEM has been shown to contribute to the creation of interactive and meaningful science learning. This study provides valuable insights as a foundation for developing innovative learning strategies and guiding more integrated future research directions.